Objects Mental Rotation under 7 Days Simulated Weightlessness Condition: An ERP Study - Wang, Hui; Duan, Jiaobo; Liao, Yang; Wang, Chuang; Li, Hongzheng; Liu, Xufeng (Frontiers in Human Neuroscience, 2017)
During the spaceflight under weightlessness condition, human’s brain function may be affected by the changes of physiological effects along with the distribution of blood and body fluids to the head. This influence on brain function will influence the performance of astronauts and therefore create possible harm to flight safety. This study intends to employ head-down tilted (HDT) bed rest model to simulate physiological effects under weightlessness condition, and use behavioural, electrophysiological techniques to compare the changes of mental rotation ability before and after short-term simulated weightlessness state. 20 males participated in the research, with the age 24.3±2.96. Behavioural results suggested that significant linear relationship existed between the rotation angle of stimuli and the reaction time. Event-related potential study results showed that there were significant difference concerning the main effect between the rotation angle and event-related potential amplitude. (F=17.000，p<0.001) In the first 3 days, the mental rotation ability changes followed “down-up-down” pattern. In the rest days it changed randomly. HDT D2 was the lowest, and HDT D3 increased gently. There was no obvious changing pattern observed after HDT 3 days. Simulated weightlessness doesn’t change the basic process of mental rotation. The effect of simulated weightlessness is neural mechanism of self-adapting. MR ability didn’t bounce back to the original level after HDT test.